Literary obscenities : U.S. case law and naturalism after modernism - Bachman, Erik M., 1981- (Refiguring modernism, 2018)
"Examines U.S. obscenity trials in the early twentieth century and how they framed a wide-ranging debate about the printed word's power to deprave, offend, and shape behavior"--Provided by publisher.